2017
DOI: 10.1371/journal.pone.0180472
|View full text |Cite
|
Sign up to set email alerts
|

Exercise before breakfast increases 24-h fat oxidation in female subjects

Abstract: BackgroundExercise performed in a postprandial state does not increase 24-h fat oxidation of male and female subjects. Conversely, it has been shown in male subjects that exercise performed in a postabsorptive state increases 24-h fat oxidation compared with that in sedentary control and that with exercise trials performed after breakfast, lunch, or dinner. There is a paucity of study evaluating the effect of exercise performed in a postabsorptive state in female subjects.MethodNine young female subjects parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…As one of its mechanism, it is suggested that it is easy to shift the fuel source from carbohydrate to fat because prior to breakfast, because it is the longer fasting condition within a day, resulting in depletion of energy derived from a carbohydrate source like glycogen (132). Similar responses are observed in women (133). Thus, acute response of fat oxidation to exercise is greater in the evening while the longer effects of exercise on fat oxidation are observed before breakfast.…”
Section: Lipid Metabolismmentioning
confidence: 96%
“…As one of its mechanism, it is suggested that it is easy to shift the fuel source from carbohydrate to fat because prior to breakfast, because it is the longer fasting condition within a day, resulting in depletion of energy derived from a carbohydrate source like glycogen (132). Similar responses are observed in women (133). Thus, acute response of fat oxidation to exercise is greater in the evening while the longer effects of exercise on fat oxidation are observed before breakfast.…”
Section: Lipid Metabolismmentioning
confidence: 96%
“…As higher fat oxidation post-exercise has an important role in exercise-induced fat loss ( 3 ), this mode of training might be an interesting approach to overcome the sedentary lifestyle associated with the lack of free time in modern life ( 4 ). Furthermore, any manipulation able to improve post-exercise fat oxidation would be an interesting approach to enhance exercise-induced health benefits ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous CHO availability is commonly manipulated as follows: 1) by an 8–12 h fasting period before training, reducing liver but not muscle glycogen ( 7 ); 2) by reducing CHO diet content for a few days, reducing mainly liver glycogen ( 8 ); 3) by performing a pre-exercise before the main exercise to reduce pre-exercise liver and muscle glycogen ( 9 ); 4) or by a combination of two or more of those approaches ( 6 , 9 ). Regardless of the different ways to manipulate CHO stores, some evidence suggests that fat oxidation over the 24-h post-exercise period is increased when exercise is performed with a certain level of CHO depletion ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…This categorical timing scheme was modeled off of prior studies . However, as noted, we further differentiated early‐ and late‐morning exercisers because of potential biological and behavioral benefits of early‐morning PA.…”
Section: Methodsmentioning
confidence: 99%
“…Exercising shortly after waking and before other obligations have a chance to interfere with PA plans may also facilitate greater PA levels. Additionally, preliminary research indicated that there may be physiological benefits of early‐morning exercise for weight control . Further examination of the relationship between PA timing and PA levels, including differentiating the potential importance of early‐ versus late‐morning exercise, is warranted.…”
Section: Introductionmentioning
confidence: 99%